2007
DOI: 10.1021/la702368b
|View full text |Cite
|
Sign up to set email alerts
|

Dwell Time Analysis of a Single-Molecule Mechanochemical Reaction

Abstract: Force-clamp spectroscopy is a novel technique for studying mechanochemistry at the single-bond level. Single disulfide bond reduction events are accurately detected as stepwise increases in the length of polyproteins that contain disulfide bonds and that are stretched at a constant force with the cantilever of an atomic force microscope (AFM). The kinetics of this reaction has been measured from single-exponential fits to ensemble averages of the reduction events. However, exponential fits are notoriously ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…By measuring the rate of disulfide reduction by E. coli thioredoxin as a function of force on an engineered cysteine bond in a polypeptide chain, Wiita and coworkers were able to deduce sub-angstrom level conformation changes in the substrate during enzyme catalysis 138 . In similar experiments, Szoszkiewicz and coworkers examined the kinetics disulfide bond reduction using MFP combined with force clamp spectroscopy 139 . Another noteworthy achievement in the field of mechanochemistry is the work of Greene and coworkers 140 who showed that the protein kinase domains of Titin unfold in a step-wise manner, and speculated that kinases in muscle cells may be activated in response to the forces generated during each contraction/relaxation cycle, i.e.…”
Section: Applications Of Afmmentioning
confidence: 99%
“…By measuring the rate of disulfide reduction by E. coli thioredoxin as a function of force on an engineered cysteine bond in a polypeptide chain, Wiita and coworkers were able to deduce sub-angstrom level conformation changes in the substrate during enzyme catalysis 138 . In similar experiments, Szoszkiewicz and coworkers examined the kinetics disulfide bond reduction using MFP combined with force clamp spectroscopy 139 . Another noteworthy achievement in the field of mechanochemistry is the work of Greene and coworkers 140 who showed that the protein kinase domains of Titin unfold in a step-wise manner, and speculated that kinases in muscle cells may be activated in response to the forces generated during each contraction/relaxation cycle, i.e.…”
Section: Applications Of Afmmentioning
confidence: 99%
“…AFM techniques have also been used to enforce chemical reactions where both bond-breaking and bond formation take place [8,9] and to investigate the rupture of covalent bonds [10]. Scanning Tunneling Microscopy (STM) is another technique that has been used to form new chemical bonds.…”
mentioning
confidence: 99%
“…Then the mean amplitudes were plotted against the transmembrane voltage, and the slope conductance of the linear regression from each point was obtained. The distributions of the dwell times of the open and closed states recorded for single BK Ca channels were obtained in a linear histogram using Clampfit (Molecular Devices) as described in a previous study (Szoszkiewicz et al, 2008). The dwell-time distributions were fitted with a single-exponential function using simplex-least-squares fitting methods (Clampfit), and the exponential time-constant (mean open or closed time) was estimated.…”
Section: Methodsmentioning
confidence: 99%